Breaking the Cycle: How Conditional Cash Transfers and Other Determinants Affect Child Labour in Indonesia - Basofi, Ahmad; ., Susilo; Badriyah, Nurul (Journal of Ecohumanism, 2025)
Economic hardship frequently forms a reason for child labour. This issue obstructs the development of human capital and perpetuates a cycle whereby children involved in works are predisposed to generate future child labourers. This persistence is mostly ascribed to the deeply rooted socioeconomic difficulties experienced by families. Government initiatives such as conditional cash transfers that alleviate the hardship are considered efficacious in addressing these fundamental concerns and reducing the incidence of child labour. However, child labour rates in Indonesia have remained unchanged over the past seven years. This research analyses the impact and effectiveness of conditional cash transfers (CCTs) as a supply-side intervention designed to enhance family welfare and prevent child labour. Employing multinomial logit analysis and Average Treatment Effect on the Treated (ATT), the results consistently indicate that whereas CCTs promote school attendance, they paradoxically increase the probability of youngsters engaging in both education and work.